PENGARUH PEMBERIAN TEPUNG KIAMBANG (Salvinia molesta) DENGAN ADITIF MULTIENZIM DALAM RANSUM TERHADAP PERFORMANS ITIK TEGAL - Sinaga R P; E Suprijatna; S Kismiati (MEDIAGRO, 2019)
ABSTRACT The research aims to determine the influence of using Salvinia molesta with multienzyme additive in rations of tegal duck performans. This research uses 72 Tegal female ducks 22 weeks old. Feed ingredients used in the reasearch consisted of corn, soybean meal, oil, bran, fish meal, premix, methionine, lysine, Salvinia molesta and multienzyme additives. The reasearch was conducted with Completely Randomized Design with 6 treatments and 4 replications of the study. Each experimental unit consists of 3 ducks. Ransum namely: T0: feed without Salvinia molesta and enzyme; T1: feed without Salvinia molesta + multienzim; T2: feed with Salvinia molesta. 5% + without multienzymes; T3: feed with Salvinia molesta. 5% + multienzim; T4: feed with Salvinia molesta. 7,5% + multienzim; T5: feed with Salvinia molesta. 10% + multienzim. The result showed no significant treatment (P> 0,05) to consumtion of ration, feed conversion and Tegal duck eeg weightbut have an effect on hen day production (P